HLA-targeted sequencing reveals the pathogenic role of HLA-B*15:02/HLA-B*13:01 in albendazole-induced liver failure: a case report and a review of the literature - Liao, Jin-Mao; Zhan, Yan; Zhang, Zheng; Cui, Jia-Jia; Yin, Ji-Ye (Frontiers in Pharmacology, 2023)
Drug-induced liver injury (DILI) is one of the serious adverse drug reactions (ADRs), which belongs to immune-mediated adverse drug reactions (IM-ADRs). As an essential health drug, albendazole has rarely been reported to cause serious liver damage. A young man in his 30 s developed severe jaundice, abnormal transaminases, and poor blood coagulation mechanism after taking albendazole, and eventually developed into severe liver failure. The patient was found heterozygous of HLA-B*15:02 and HLA-B*13:01 through HLA-targeted sequencing, which may have a pathogenic role in the disease. This case report summarizes his presentation, treatment, and prognosis. A useful summary of the diagnosis and associated genetic variant information is provided.